Cost-effectiveness of cemiplimab plus chemotherapy versus chemotherapy for the treatment of advanced non-small cell lung cancer - Liang, Xueyan; Chen, Xiaoyu; Li, Huijuan; Li, Yan (Frontiers in Oncology, 2023)
Background In patients with advanced non-small cell lung cancer (aNSCLC), cemiplimab plus chemotherapy prolonged overall survival (OS) and progression-free survival (PFS) significantly compared to chemotherapy alone. The cost-effectiveness of these drugs is still uncertain. The aim of this study is to assess the cost-effectiveness of cemiplimab plus chemotherapy compared with chemotherapy for the treatment of aNSCLC from the third-party payer perspective in the United States. Materials and methods The cost-effectiveness of cemiplimab with chemotherapy versus chemotherapy for the treatment of aNSCLC was evaluated using a partitioned survival model containing three mutually incompatible health states. The clinical characteristics and outcomes used in the model were gathered from EMPOWER-Lung 3 trial. We have conducted deterministic one-way sensitivity analysis and probabilistic sensitivity analysis in order to evaluate the robustness of the model. The primary outcomes considered were the costs, life-years, quality-adjusted life-years (QALYs), incremental cost-effectiveness ratio (ICER), incremental net health benefits (INHB), and incremental net monetary benefits (INMB). Results Treatment of aNSCLC with cemiplimab plus chemotherapy increased efficacy by 0.237 QALYs and was associated with an increased total cost of $50,796 compared to chemotherapy alone, resulting in an ICER of $214,256/QALY gained. At a WTP threshold of $150,000/QALY, the INHB of cemiplimab plus chemotherapy was 0.203 QALYs and the INMB was $304,704 compared to chemotherapy alone. The probabilistic sensitivity analysis revealed that there was only a 0.04% chance that cemiplimab with chemotherapy would be cost-effective at a WTP threshold of $150,000/QALY. The performance of model was mainly determined by the price of cemiplimab, according to a one-way sensitivity analysis. Conclusions From the third-party payer perspective, cemiplimab combined chemotherapy is unlikely to be a cost-effective option for the treatment of aNSCLC at the WTP threshold of $150,000/QALY in the United States.